P3.320 Unlinked Anonymous Testing For Monitoring HIV Prevalence in Sentinel Groups in Slovenia, 2002–2011. (13th July 2013) - Klavs, I; Kastelic, Z; Kustec, T; Poljak, M
Abstract : Background: In addition to universal mandatory HIV/AIDS case reporting for HIV surveillance purposes, we also monitor HIV prevalence in several sentinel populations at higher risk (injecting drug users (IDU), men who have sex with men (MSM), patients with sexually transmitted infections (STI)) and one low risk group (pregnant women). Methods: During 2002–2011, we continuously sampled residual sera from STI patients tested for syphilis and every second year, residual sera from pregnant women screened for syphilis in several laboratories. Saliva specimens were continuously voluntarily obtained from IDU entering a substitution treatment programme and also, but for three months per year only, from IDU attending a harm reduction programme. Once per year, we obtained saliva specimens from MSM attending an MSM event. Specimens were labelled only with the type of sentinel population, sampling year, sex, and age group and were tested for anti-HIV antibodies. Results: 1, 066 saliva specimens were collected from MSM, 2, 048 saliva specimens from IDU, 6, 327 serum specimens from patients with STI, and 39, 818 serum specimens from pregnant women. Annual prevalence estimates for MSM varied between 0% in 2002 and 7.6% in 2011, for patients with STI between 0.2% in 2003 and 2.7% in 2008, and for pregnancies from 0% in 2003 and 2007 to 0.03% in 2011. Among IDU specimens, only two tested anti-HIV positive, one in 2010 and one in 2011 (0.4% and 0.5% respectively). Conclusions: Our results indicate a disproportionally high and rising HIV infection prevalence among MSM that has increased above 5% in 2011. HIV infection prevalence among pregnancies has remained rather low, however, the highest ever (0.5%) has been estimated in 2011. Promotion of safer sexual behaviour and HIV testing among MSM as well as positive prevention among MSM with HIV diagnosis are urgently needed. The introduction of HIV screening of pregnancies should be considered.